Food Prices and Body Fatness among Youths - Michael Grossman; Erdal Tekin; Roy Wada (Institute for the Study of Labor (IZA), 2013)
In this paper, we examine the effect of food prices on clinical measures of obesity, including body mass index (BMI) and percentage body fat (PBF) measures derived from bioelectrical impedance analysis (BIA) and dual energy x-ray absorptiometry (DXA), among youths ages 12 through 18. The empirical analyses employ data from various waves of the National Health and Nutrition Examination Survey (NHANES) merged with several food prices measured by county and year. This is the first study to consider clinically measured levels of body composition rather than BMI to investigate the effects of food prices on obesity among youths. We also examine whether the effects of food prices on body composition differ by gender and race/ethnicity. Our findings suggest that increases in the real price of one calorie in food for home consumption and the real price of fast-food restaurant food lead to improvements in obesity outcomes among youths. We also find that an increase in the real price of fruits and vegetables has negative consequences for these outcomes. Finally, our results indicate that measures of PBF derived from BIA and DXA are no less sensitive and in some cases more sensitive to the prices just mentioned than BMI.
Keywords: I1; I18; 330; food price; obesity; body fat; BMI